Luminescence and impedance analysis of CaSiO3:Tb3+ nanophosphors material prepared by combustion method for OLED - Verma, Ohm Prakash; Verma, Shailendra; Meshram, MR; Singh, Nirbhay K (International Journal of Computer Sciences and Engineering, 2019)
Calcium Silicate acquires a higher luminous efficiency when it is doped with rare earth activated ions. The luminescence behaviour of unhoped CaSiO3 was investigated by a very few research groups. Effect of Tb3+ ion composition on the structural and phosphorescence properties from CaSiO3:Tb3+ nanocrystals has been evaluated using powders grown by the solution combustion technique. The surface morphology were analyzed by SEM and the chemical composition of phosphor characterized by EDX analysis. The XRD study indicates that as the terbium concentration increases the phase changes from CaSiO3 to Ca3Si2O7. Broad band emissions peaking between 280 - 360 nm derived from excited states of Tb3+ ions were observed for all powders grown from various Tb compositions. The green emission transition at 550nm due to an electronic transition of 5D4-7F5 was found to be more prominent and intense. Intensity of afterglow phosphorescence was greatly influenced by the composition of the activator ions. It is found that the composition shows optimum PL properties at 7% of terbium Tb3+ ions concentration. The impedance spectroscopic study shows that the present phosphor shows electrical behavior like dielectric material in AC field. The activation energy of phosphor analysed by Chem’s imperials formula in thermoluminescence analysis found to be.0.86eV. It is found that the prepared luminesce material is a new alternative for making cheap green organic light emitting diodes(OLED’s).